Extramucosal Formation and Prognostic Value of Secretory Antibodies in Rheumatoid Arthritis. Issue 5 (28th March 2022) - Martinsson, Klara; Kling, Lovisa Lyttbacka; Roos‐Ljungberg, Karin; Griazeva, Irina; Samoylovich, Marina; Paul, Stephane; Rönnelid, Johan; Weitoft, Tomas; Wetterö, Jonas; Kastbom, Alf
Abstract : Objective: To investigate levels and possible extramucosal formation of secretory Ig, including anti–citrullinated protein antibodies (ACPAs), in rheumatoid arthritis (RA). Methods: Three patient groups were studied: 1) ACPA‐positive patients with musculoskeletal pain without clinical arthritis, 2) patients with recent‐onset RA, and 3) patients with established RA. In baseline serum samples (groups 1 and 2) and paired synovial fluid samples (group 3), we analyzed total secretory IgA, total secretory IgM, free secretory component (SC), and SC‐containing ACPA. Extramucosal formation of SC‐containing ACPA was investigated by preincubating RA sera and affinity‐purified ACPA with recombinant free SC. Results: Compared to healthy controls, serum levels of total secretory IgA and total secretory IgM were increased both in patients with early RA and at‐risk patients ( P  < 0.05). Patients with early RA with elevated total secretory Ig had significantly higher disease activity during the 3‐year follow‐up period compared to those without increased levels. At‐risk patients who developed arthritis during follow‐up (39 of 82) had higher baseline total secretory IgA levels compared to those who did not ( P  = 0.041). In established RA, total secretory IgA and total secretory IgM levels were higher in serum than in synovial fluid ( P  < 0.0001), but SC‐containing ACPAs adjusted for total secretory Ig concentration were higher in synovial fluid ( P  < 0.0001). Preincubation with recombinant free SC yielded increased SC‐containing ACPA reactivity in sera as well as in affinity‐purified IgA and IgM ACPA preparations. Conclusion: Circulating secretory Ig are elevated before and at RA onset. In the presence of free SC, secretory Ig may form outside the mucosa, and SC‐containing ACPAs are enriched in RA joints. These findings shed important new light on the mucosal connection in RA development.